Toward energy security: The role of industrial intelligence and high-quality economic development - Ul-Haq, Jabbar; Visas, Hubert; Rehan, Raja; Hye, Qazi Muhammad Adnan; Abbasi, Shujaat (International Journal of Management and Sustainability, 2025)
Promoting energy security is an effective strategy for achieving sustainable development. However, rising energy demand has raised fears about energy insecurity (EIS), which poses a significant challenge for many nations. Industrial intelligence (IndInt) can help modernize the production process by promoting energy efficiency, green technology, and cost savings. Given the importance of industrial intelligence in promoting energy security, our study investigates the impact of industrial intelligence and high-quality economic development (HQED) on EIS in China, using data from Chinese provinces from 2007 to 2017. For empirical investigation, a fixed-effects model with Driscoll-Kraay standard errors (FE-DKSEs) is employed. For the sake of robustness, feasible generalized least squares (FGLS) and panel-corrected standard errors (PCSEs) are also applied. Based on the study results, the relationship between industrial intelligence and EIS is non-linear and statistically significant. HQED and EIS are negatively associated, showing that HQED significantly contributes to mitigating EIS. Moreover, the moderating role of HQED in EIS reduction through industrial intelligence is demonstrated. Further, our study findings are robust to the inclusion of various controls. Urbanization and exports increase EIS. Industrial intelligence is helpful in achieving energy security in China. The government should devise policies that promote industrial intelligence to achieve energy security, as energy security is a prerequisite for sustainable development.